Internalization of Islamic Values through the Majlis of the Congregational Prayer Movement - Fikri Farikhin (JURNAL ILMIAH GEMA PERENCANA, 2024)
Islamic values constitute an essential foundation in shaping the character and behavior of Muslims. However, many members of society have limited understanding and practice of these values in their daily lives, a condition exacerbated by restricted access to formal religious education such as madrasahs. This study aims to explore the process of internalizing Islamic values through the Majlis Gerakan Shalat Berjamaah (GSB), the factors influencing its effectiveness, and the implications of participation in GSB for the appreciation and practice of Islamic values among members and the wider community. This study employs a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and document analysis tailored to field phenomena. The internalization of Islamic values within GSB is carried out through invitations to perform congregational dawn prayers (Shalat Subuh berjamaah), followed by spiritual studies led by Kiai, and implemented consistently (istiqomah). Factors influencing the effectiveness of this internalization include the role of GSB leaders and the enthusiasm of the congregation. The positive impact of participation in GSB is reflected in increased worship motivation among members and a growing number of congregants attending the mosque.